Physicochemical Characteristics of Cascara Tea Made from Arabica Coffee Skin with the Addition of Secang Wood (Caesalpinia Sappan L.) - Faradilah Karim; Novita Sari Parenden; Zulkahfi Zulkahfi; Titi Wahyuni; Fitri Sylvianti Titong (Jurnal Penelitian Kehutanan BONITA, 2026)
Coffee is one of the leading commodities in Mamasa Regency, West Sulawesi Province. Increasing coffee harvests have an impact on the amount of coffee husk waste produced. Coffee husk waste is usually only used as animal feed, fertilizer, and sometimes directly discarded, which has the potential to cause environmental pollution. This study aims to utilize coffee husk waste into products that have economic value by diversifying the processing, namely cascara tea with the addition of sappanwood extract. Cascara tea is a beverage product made from coffee husks (read cherry) as the basic ingredient that has a color and taste similar to tea. This study used a quantitative approach with experimental tests. Phytochemical analysis used the Analysis of Variance (ANOVA) method and continued with the Duncan Multiple Range Test (DMRT). The results showed that cascara tea is made by sorting and cleaning the coffee husk, drying, reducing the size, adding sappanwood powder, brewing and filtering to produce cascara tea. The results of the physicochemical tests to determine the quality of cascara tea products for each parameter were: moisture content of 10.8-11.7%, ash content of 6.9-7.3%, and pH value of 4.3-4.4. The organoleptic test results showed that sample P3 (ratio of 3 g coffee skin + 0.39 g sappan wood) was preferred by the panelists because it had a distinctive aromatic color, aroma and taste